2017
DOI: 10.5812/intjsh.13162
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Self-Esteem and Attributional Styles with Self-Handicapping in Primary Schools

Abstract: Background: Self-esteem, attributional styles, and self-handicapping play key roles in students' individual and social performances. Through determining interactional relations among these factors, parents and schools can plan for improving students' performances. Objectives: Hence, this study aimed to investigate the relationship of self-esteem and attributional styles with self-handicapping among primary school students. Methods: The statistical population of this study comprised of 3rd to 5th grades of prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The transplantation of allogeneic [ 58 , 59 , 60 , 61 ] and iPS-derived [ 62 , 63 ] myoblasts and myogenic precursor/progenitor cells, muscle satellite cells [ 64 ], mesoangioblasts [ 65 ], and mesenchymal stem cells [ 66 , 67 , 68 ] in both preclinical experiments and clinical trials has been reported and limited positive effects demonstrated. Inadequate cell engraftment, their low proliferative potential and chronic systemic, and local inflammation in the affected muscles were named the main reasons for the insufficient efficacy of single cell type cell therapy of the disease [ 69 , 70 ].…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 99%
“…The transplantation of allogeneic [ 58 , 59 , 60 , 61 ] and iPS-derived [ 62 , 63 ] myoblasts and myogenic precursor/progenitor cells, muscle satellite cells [ 64 ], mesoangioblasts [ 65 ], and mesenchymal stem cells [ 66 , 67 , 68 ] in both preclinical experiments and clinical trials has been reported and limited positive effects demonstrated. Inadequate cell engraftment, their low proliferative potential and chronic systemic, and local inflammation in the affected muscles were named the main reasons for the insufficient efficacy of single cell type cell therapy of the disease [ 69 , 70 ].…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 99%